Analisis Kesalahan Siswa dalam Pemecahan Masalah Aritmatika Sosial - Iriyanti Iriyanti; Hari Tenang (Universitas Pancasakti Tegal, 2019)
This study aims to determine the types of errors in solving Social Arithmetic problems using Newman error analysis, for profit and loss learning material for 7C grade students at SMPN 4 Pandak, Bantul. Research subjects were 27 students, data collection techniques using written tests and clinical interviews. The written test consists of 3 questions about Social Arithmetic about profit and loss. The test results show that in question number 1 there were 6 students wrong, question number 2 there were 26 students wrong and in question number 3 all students' answers were wrong. Then the results of the work of 3 students who had the most errors were chosen at the completion of the three test questions for further analysis. Analysis of the results of errors was carried out based on the type of error Newman and identified that in problem number 1 there were 6 students making mistakes type 2, 3, 4, and 5; in question number 2 there were 26 students who mostly made mistakes of types 2 and 3; in question number 3 there are no correct student answers, all students make mistakes on types 2 and 3 and most of them on type 4 errors.